APPROACHES FOR ENHANCING THE BIOAVAILABILITY OF ACYCLOVIR: A CRITICAL REVIEW - R SANKAR; S JAIN (International Journal of Pharma and Bio Sciences, 2013)
Acyclovir, a purine nucleoside analogue, is a promising antiviral compound effective against Herpes Simplex Virus (HSV), Varicella-Zoster Virus (VZV), Epstein-Barr virus (EBV), and Cytomegalovirus (CMV). From the past 3 decades, it has been extensively exploited by the scientists for the diseases caused by these infective viruses. Upto a certain extent they are able to make dosage forms which can treat the infections caused by these viruses but, cannot perfectly/completely cure the ailments. In spite of its effective antiviral activity, oral bioavailability of Acyclovir is low (15 to 30%) and highly variable. This review discusses various possible reasons for the poor oral bioavailability of Acyclovir. In addition, it also focuses on various formulation approaches investigated by formulation scientists for the improvement of its oral bioavailability such as self microemulsifying drug delivery system, gastroretentive mucoadhesive microspheres, microemulsions, niosomes etc.Though the reasons for the poor oral bioavailability of Acyclovir are conflicting and inconclusive, many authors have reported widely varying formulation approaches to circumvent this problem and results suggested that these dosage forms can take place in the market. However detailed clinical studies are still needed to reconfirm these findings. The present review critically analyzes the pharmacokinetic and clinical limitations of conventional therapy of Acyclovir and different formulation strategies taken by the research scientists to overcome its formulation and clinical limitations.